Association Between High-Sensitivity C-Reactive Protein Levels and Metabolic Dysfunction-Associated Steatotic Liver Disease and Liver Fibrosis Risk: A Study Based on NHANES Data - Xu, Chaolong; Wang, Kai; Peng, Zhiming; Chen, Peng; Zhang, Chengchen; Zeng, Xianyi; Tan, Chenghao; Huang, Yunchen (Turkish Journal of Gastroenterology, 2025)
Background/Aims: High-sensitivity C-reactive protein (hs-CRP) is a known inflammatory biomarker linked to various metabolic disorders. This study sought to examine the association between hs-CRP levels and the risk of metabolic dysfunction-associated steatotic liver disease (MASLD) and liver fibrosis (LF). Materials and Methods: Data from 2787 participants of the 2017-2020 National Health and Nutrition Examination Survey were analyzed. The evaluation of liver steatosis and fibrosis was performed using transient elastography. Furthermore, logistic regression models were applied to examine the correlation between 4 categorized levels of hs-CRP and the risks of MASLD and LF. Results: Compared to individuals with hs-CRP ≤3 mg/L, those with hs-CRP levels of 3.01-6 mg/L, 6.01-10 mg/L, and ≥10.01 mg/L exhibited markedly increased risks of MASLD, with odds ratios and 95% CI of 2.229 (1.892-2.625), 2.474 (1.982-3.090), and 3.175 (2.497-4.037), respectively. The receiver operating characteristic and calibration curves of the model validated the significant association of higher hs-CRP levels with increased MASLD and LF risk. Conclusion: Elevated hs-CRP levels are prominently associated with increased risks of MASLD and LF. High-sensitivity C-reactive protein could serve as a potential biomarker for identifying and managing MASLD and related fibrosis risks. Cite this article as: Xu C, Wang K, Peng Z, et al. Association between high-sensitivity C-reactive protein levels and metabolic dysfunction-associated steatotic liver disease and liver fibrosis risk: A study based on NHANES data.Turk J Gastroenterol. 2025;36(9):590-599.